Effect of Westwood (Cirina forda) Larva Meal on the Laying Performance and Egg Characteristics of Laying Hen in a Tropical Environment - Amao, O.A.; Oladunjoye, I.O.; Togun, V.A.; Olubajo, K.; Oyaniyi, O. (International Journal of Poultry Science, 2010)
Two hundred and fifty Isa-Brown point of lay chicken of 30 weeks of age were used to determine the effect of substituting westwood (Cirina forda) larva meal (WWLM) for fish meal which is the most expensive feed ingredient in layer diet on laying performance of chicken. The birds were fed five diets in which WWLM replaced 0, 25, 50, 75 and 100% fish meal. Data collected were feed intake, weight change, egg production, feed efficiency and egg quality characteristics Data were analyzed using one-way analysis of variance. Proximate analysis showed that WWLM contained higher crude protein, crude fibre, ether extract, dry matter and ash than fish meal. Feed intake and weight gain were not significantly (p